A Simplistic Approach for Assessing Hydroclimatic Vulnerability of Lakes and Reservoirs with Regulated Superficial Outflow - Demertzi, Kleoniki; Papadimos, D.; V. Aschonitis; D. Papamichail (2019)
Demertzi, K.; Papadimos, D.; Aschonitis, V.; Papamichail, D. A Simplistic Approach for Assessing Hydroclimatic Vulnerability of Lakes and Reservoirs with Regulated Superficial Outflow. Hydrology 2019, 6, 61